A family of Drosophila serotonin receptors with distinct intracellular signalling properties and expression patterns. - Saudou, F (1992)
Biogenic amines such as serotonin elicit or modulate a wide range of behaviours by interacting with multiple receptor subtypes. We have isolated cDNA clones encoding three distinct Drosophila serotonin receptors which belong to the G protein-coupled receptor family. When expressed in mammalian cells, these receptors activate different intracellular effector systems. The 5HT-dro1 receptor stimulates adenylate cyclase while the 5HT-dro2A and the 5HT-dro2B receptors inhibit adenylate cyclase and activate phospholipase C. Expression of all three receptors starts in late embryos and is restricted to distinct populations of cells in the central nervous system. The 5HT-dro2A receptor is predominantly expressed in midline motor neurons (VUM neurons) that innervate larval muscles thus suggesting a role for this receptor in motor control.